EXAMINING CURRICULUM CONTENT: INVESTIGATING HOW TO KEEP DISTANCE EDUCATION STUDENTS ENGAGE - Mehmood Bhuttah, Tariq; Xiaoduan, Chen; Ullah, Hakim (International Journal of Research -GRANTHAALAYAH, 2018)
Distance education is popular among the education students of the Virtual University. This study aims to examine the current curriculum content in distance education to gauge if they are still able to keep the students engaged. To be able to do that, a variety of ICT technologies have been set up in the university to cater to the needs of the distance education students majoring in educational management. A qualitative methodology was used specifically using semi-structured interviews on ten randomly chosen respondents representing all the four years of college study, and a representative for each gender. This was done to capture all the possible answers they may give in terms of their cultural backgrounds, their gender and their social status. The results showed that among their five lessons for this semester, the most popular were Conflict Resolution and Community Relations. The least popular was school finance. In terms of the level of engagement and interest levels, most of the respondents had high scores of 9 and above which showed their high interest in the course they are studying. The presence of the ICT technology has definitely enhanced their experience and most respondents have said that they are very thankful for the experiences they’ve had with the learning management systems (LMS) because it allowed them to interact with their co-students and teachers from Taiwan. These interactions have served as the respondents’ bridge to learning how other cultures teach these particular topics and how they process their learnings as well.